2017
DOI: 10.1101/192062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudomonas aeruginosatype IV minor pilins and PilY1 regulate virulence by modulating FimS-AlgR activity

Abstract: 10Type IV pili are expressed by a wide range of prokaryotes, including the opportunistic 11 pathogen Pseudomonas aeruginosa. These flexible fibres mediate twitching motility, biofilm 12 maturation, surface adhesion, and virulence. The pilus is composed mainly of major pilin 13 subunits while the low abundance minor pilins FimU-PilVWXE, plus the putative adhesin PilY1, 14 prime pilus assembly and are proposed to form the pilus tip. The minor pilins and PilY1 are 15 encoded in an operon that is positively regula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 108 publications
1
6
0
Order By: Relevance
“…It is generally thought that a mucoid strain would produce more EPS (Marko et al , ), and this is in agreement with our results that the mucoid pilN mutant produced enhanced EPS compared to the wild‐type strain. In addition, increased biofilm formation was observed in the pilN mutant, consistent with previous reports showing that EPS production has a positive correlation with biofilm formation in Xanthomonas species (Buttner and Bonas, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is generally thought that a mucoid strain would produce more EPS (Marko et al , ), and this is in agreement with our results that the mucoid pilN mutant produced enhanced EPS compared to the wild‐type strain. In addition, increased biofilm formation was observed in the pilN mutant, consistent with previous reports showing that EPS production has a positive correlation with biofilm formation in Xanthomonas species (Buttner and Bonas, ).…”
Section: Discussionsupporting
confidence: 93%
“…The qualitative analysis and quantitative measurement by crystal violet staining showed that PΔ pilN had greater biofilm production than the wild type, whilst biofilm production in the complementary strain CPΔ pilN was similar to the wild type (Figure a). The phenotype of mucoid colony of PΔ pilN was speculated to be related to the EPS production (Rosenberg et al , ; Marko et al , ). Therefore, the production of EPS was compared between the wild type PXO99 A , PΔ pilN , and CPΔ pilN .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the pilus base, the inner membrane protein PilC and cytoplasmic ATPase motors, PilB and PilT, catalyze polymerization and depolymerization, respectively (McCallum et al, 2017(McCallum et al, , 2019a. Minor pilins and PilY1 initiate pilus polymerization and are thus thought to localize at the pilus tip (Marko et al, 2018;Nguyen et al, 2015). The pilus exits the periplasm through an outer membrane pore formed by PilQ oligomers.…”
Section: Introductionmentioning
confidence: 99%